ANALISIS AGRIBISNIS JERUK SIAM (Citrus nobilis lourvar) DI KECAMATAN KUOK KABUPATEN KAMPAR - Dewi, Eka Rahmina; Hadi, Syaiful; Edwina, Susy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to analyze the agribusiness of Orange Siam in Kuok Subdistrict. This study was conducted in Kuok Subdistrict, Kampar District. The respondent technique was taken by purposive sampling with 34 farmers. The results showed that the upstream agribusiness subsystem was in the right category. On farm agribusiness subsystem, orange siam farmer spend the production cost of farming amounted to Rp. 35.042.645/Ha/year. The gross revenues received by the orange siam farmer amounted to Rp. 71.853.659/Ha/year with average production is 4.970 Kg/Ha/year. Net income received by the orange siam farmers of Rp. 36.811.014/Ha/ with Benefit Cost Ratio (BCR) > 1.05. Downstream agribusiness related to post-harvest handling by orange siam farmer only fruit collection and fruit sorting activities. Marketing subsystem related marketing channel of orange siam farmers in Kuok Subdistrict consists of 3 marketing channels, that is farmer-consumer, farmer-retailer-consumer, and farmer-wholesalers-retailer-consumer. Supporting institutional subsystem in Kuok Subdistrict are government institution, agricurtural extension institutes, and farmer groups. Keywords : Agribusiness, Orange Siam, Benefit Cost Ratio